Personalising Learning: Do Teachers Use Student Voice and Choice at Secondary School? - Mikhail N. Shchevliagin; Diana O. Koroleva (Вопросы образования)
The article is dedicated to the modern concept “student voice and choice,” which is an essential component of personalised learning. The research was conducted in the Russian schools that integrated the educational platform with personalised learning methodology, “SberClass.” On the basis of 24 interviews with the teachers the article: